2019
DOI: 10.1016/j.jcot.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of sternoclavicular joint septic arthritis

Abstract: Introduction: Infections of the sternoclavicular joint (SCJ) account for less than 1% of all joint infections. There are no standardized diagnostic and therapeutic algorithms defined in literature. This study intended to report the risk factors, the bacterial spectrum, the extent and localization and the clinical outcome of SCJ infections. Patients and methods: We retrospectively reviewed the medical charts of 13 patients (8 men, five women, mean age 37.6 years) with SCJ infections between Januray 1st 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 30 publications
(54 reference statements)
0
42
0
6
Order By: Relevance
“…Overall, complication rates varied from 0% (Jang et al) to 40% (Bakaeen et al. and Puri et al) [ 4 , 15 , 16 , 21 ]. The mean follow-up ranged from three months (Von Glinski et al) to 53 months (Jang et al), as shown in Table 6 [ 4 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, complication rates varied from 0% (Jang et al) to 40% (Bakaeen et al. and Puri et al) [ 4 , 15 , 16 , 21 ]. The mean follow-up ranged from three months (Von Glinski et al) to 53 months (Jang et al), as shown in Table 6 [ 4 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…), and 23% (Von Glinksi et. al) [ 1 , 3 , 13 , 21 ]. Two of these studies further stratified the recurrence of infection by treatment modality and/or closure technique.…”
Section: Reviewmentioning
confidence: 99%
“…In fact, histopathological examination of the bone and soft tissue of the SCJ obtained intraoperatively revealed that bone destruction and granulation tissue formation were advanced, along with signs of osteomyelitis. Although there are no standardized diagnostic algorithms for pyogenic arthritis of the SCJ 9) , diagnosis is based on the above-mentioned clinical and image findings such as bone destruction, joint space enlargement, and infectious complications by ultrasound, radiography, CT, and MRI. Gram stain and culture of joint fluid obtained by arthrocentesis and blood revealed a bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Any remaining infected bone or cartilage may cause reinfection 12) . If the infection involves a wide area, adequate surgical management is required, including SCJ and rib resection 9) . Careful attention should be paid not to damage the adjacent great vessels, and cooperation with other departments such as thoracic surgery and orthopedic surgery is essential during surgery in the SCJ, posterior sternum, and thorax area.…”
Section: Discussionmentioning
confidence: 99%
“…Запальне ураження ГКС -рідке захворювання, що потребує хірургічного лікування [1,2]. Інфекція ГКС в більшості випадків асоційована з цукровим діабетом, ін'єкційною наркотичною залежністю, лікуванням імуносупресорами, ревматичними хворобами [2,3,4,5]. На початкових етапах розвитку хвороби місцеві зміни незначні, а диференційний ряд болю в ділянці суглобу включає нехірургічні захворювання [6,7].…”
Section: вступunclassified